Pengaruh E-Wom terhadap Minat Beli Produk Sayuran - Numan Hapidudin; Tresna Wiwitan (UNISBA Press, 2024)
Abstract. The increasing growth of internet users makes it easier for businesses to market their services and products. E-commerce is the use of computer networks to carry out business processes. One of the things that can generate consumer buying interest is the influence of positive or negative information called electronic word of mouth. Based on this phenomenon, the objectives in this study are to determine: (1) the effect of intensity on buying interest in vegetable products through the EdenFarm application (2) the effect of valence of opinion on buying interest in vegetable products through the EdenFarm application (3) the effect of content on buying interest in vegetable products through the EdenFarm application. The theory used is: Diffusion of Innovation, and using the concepts of Marketing Communication, marketing communication and marketing mix, e-commerce. This research uses quantitative methods using simple linear regression analysis tests. The data analysis techniques used in this research are descriptive analysis techniques and inferential analysis techniques. The population in this study were consumers who reviewed vegetable products in the EdenFarm application and the sample in this study amounted to 112 people. the sampling technique is simple random sampling. The results of the simple linear regression test significance value show the value of 0.000 <0.05, therefore it can be seen that E-Wom has a positive influence on consumer buying interest in vegetable products in the EdenFarm application. Abstrak. Meningkatnya pertumbuhan pengguna internet mempermudah pelaku usaha dalam memasarkan jasa maupun produk yang dimilikinya. E-commerce adalah penggunaan jaringan komputer untuk menjalankan proses bisnis. Salah satu hal yang dapat menimbulkan minat beli konsumen adalah pengaruh informasi positif atau negatif yang disebut dengan electronic word of mouth. Berdasarkan fenomena tersebut, tujuan dalam penelitian ini adalah untuk mengetahui : (1) pengaruh intensity terhadap minat beli produk sayuran melalui aplikasi EdenFarm (2) pengaruh valence of opinion terhadap minat beli produk sayuran melalui aplikasi EdenFarm (3) pengaruh content terhadap minat beli produk sayuran melalui aplikasi EdenFarm. Teori yang di gunakan yaitu: Difusi Inovasi, dan menggunakan konsep Komunikasi Pemasaran, marketing communication dan marketing mix, e-commerce. Penelitian ini menggunakan metode kuantitatif dengan menggunakan uji analisis regresi linier sederhana. Teknik analisis data yang digunakan dalam penelitian ini adalah teknis analisis deskriptif dan teknik analisis inferensial. Populasi pada penelitian ini merupakan konsumen yang memberikan ulasan produk sayuran di aplikasi EdenFarm dan sampel pada penelitian ini berjumlah 112 orang. teknik pengambilan sampel yaitu simple random sampling. Hasil uji regresi linier sederhana nilai signifikansi menunjukan hasil nilai 0,000 < 0,05, maka dari itu dapat diketahui bahwa E-Wom memiliki pengaruh positif terhadap minat beli konsumen pada produk sayuran di aplikasi EdenFarm.